JAVANESE SCRIPT HANACARAKA CHARACTER PREDICTION WITH RESNET-18 ARCHITECTURE - Sudewo, Egi Dio Bagus; Biddinika, Muhammad Kunta; Fadlil, Abdul (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: This study aims to train computers to recognize Javanese script characters known as Hanacaraka. The evaluation was conducted on the use of Convolutional Neural Network (CNN) with the ResNet-18 architecture in recognizing these characters. The research objective is to overcome traditional character recognition barriers and improve accuracy. The method employed includes building a CNN model with the ResNet-18 architecture and using diverse datasets. The results show a training accuracy of 100%, validation accuracy of 98.01%, and accuracy, precision, recall, and F1-score each at 100%. This study concludes that the developed model successfully achieves a high level of accuracy and contributes positively to the development of Javanese Hanacaraka character recognition technology. Keywords: convolution neural network (CNN); javanese hanacaraka script; resnet-18           Abstrak: Penelitian ini bertujuan melatih komputer untuk mengenali huruf aksara Jawa Hanacaraka. Evaluasi dilakukan terhadap penggunaan Convolutional Neural Network (CNN) dengan arsitektur ResNet-18 dalam pengenalan karakter tersebut. Tujuan penelitian adalah mengatasi hambatan pengenalan karakter tradisional dan meningkatkan akurasi. Metode yang digunakan mencakup pembuatan model CNN dengan arsitektur ResNet-18 dan penggunaan dataset yang beragam. Hasilnya menunjukkan akurasi pelatihan 100%, validasi 98.01%, dan akurasi, presisi, recall, dan F1-score masing-masing sebesar 100%. Simpulan penelitian ini adalah bahwa model yang dikembangkan berhasil mencapai tingkat akurasi yang tinggi dan memberikan kontribusi positif pada pengembangan teknologi pengenalan karakter Hanacaraka Jawa.Kata kunci: convolution neural network (CNN); huruf aksara jawa hanacaraka; resnet-18